New Business Creation Systems for Institutionalized Radical Innovation Management - Hartmann, Philipp; SpringerLink (Online service) (Wiesbaden : Springer Fachmedien Wiesbaden : Imprint: Springer Gabler, 2014)
Established companies are facing an increasingly dynamic and globalized competitive environment. Radical innovations are considered a means to escape this trend. In particular, it is desirable for established companies to institutionalize systems to repeatedly create new business based on radical innovations (New Business Creation, NBC). In six in-depth case studies, Philipp Hartmann identifies design variables for NBC systems and explores related performance measurement activities. In a subsequent cross-case comparison, idiosyncratic observations are synthesized into thirteen propositions. Moreover, two structurally different approaches to NBC are identified and discussed. In addition, the present research thoroughly studies performance measurement activities in the context of NBC activities and finds that they are an essential component that has been insufficiently addressed by existing theory. Contents Literature Review (Innovation Management, NBC, Performance Measurement) Performance Measurement in an NBC context (Individual Case Studies and Cross-case Analysis) Target Groups Researcher and students of innovation management, strategic management, management control Innovation manager, business development, controlling The Author Philipp Hartmann received his degree in industrial engineering from the Berlin Institute of Technology and holds a Diplôme de Grande Ecole from ESCP Europe, Paris. He is an early stage technology investor at Index Ventures and worked in investment banking.
Keywords: Economics; Economics/Management Science; Innovation/Technology Management; Business/Management Science, general